SENTENCE SELECTION METHODS FOR TEXT SUMMARIZATION - Guran, Aysun; Arslan, Sumeyra Nur; Kilic, Esma; Diri, Banu (IEEE, 2014)
The aim of this work is to create text summaries by selecting the most important sentences of documents. For this aim 15 sentence selection methods are used. These methods are compared on the evaluation set created by 15 women and 15 men evaluators. The performance results of the systems that are obtained by using different sentence selecetion methods together are also analyzed and the results are shared.
Keywords: text summarization; sentence selection methods; name entity recognition; Engineering; Telecommunications